Synthesis with Improved Yield and Study on the Analgesic Effect of 2-Methoxyphencyclidine - Ahmadi, Abbas; Mahmoudi, Ali (Arzneimittelforschung, 2006)
Phencyclidine (1-(1-phenylcyclohexyl)piperidine, CAS 956-90-1, PCP) has shown analgesic effects. Some of its derivatives have been synthesized and their biological properties were studied. Since a methoxy group has been added to the position 2 of the cyclohexane ring of PCP, the resulting compound is more polar than PCP. This compound was synthesized using an improved method with a higher yield. Its analgesic effect was studied using the tail-flick test on rats and was compared with that of ketamine (CAS 1867–66–9).The results showed that 2-methoxyphencyclidine increased tail-flick latencies as compared to the control group. The maximum analgesic effect of the compound occurred 5–10 min after its injection, while the effect of ketamine was observed 10–25 min after injection.
Keywords: Analgesics; CAS 956-90-1; 2-Methoxyphencyclidine, analgesic effect, rat, synthesis; Phencyclidine derivatives